The Representation of Racism in The Man Who Knew Infinity Movie by Matthew Brown - Siti Ayu Wulandari; Rasiah; Rahmawati Azi (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2022)
This study aimed to analyze racism in The Man Who Knew Infinity movie used Paradies, Harris, and Anderson’s theory. The Man Who Knew Infinity that released in 2016 is a film directed by Matthew Brown that features the character of a genius mathematician from India named Srinivasa Ramanujan who wants to publish his formula about mathematics in Trinity College. As an Indian, Ramanujan experienced various acts of racism committed by the British, both mentally and physically. This study used a descriptive qualitative method. The data collected through four steps, such as watching, screenshotting, note taking, and identifying the data. The result of this study showed that the main character experienced racism because of his race and nationality. The kinds of racism that the main character experienced namely stereotypes, prejudice, and discrimination. Keywords: Racism, stereotypes, prejudice, discrimination